Efektifitas Pelayanan Jemput Bola Kartu Identitas Anak (KIA) Dinas Kependudukan Dan Pencatatan Sipil Kota Payakumbuh - Brianda, Wiko Okta; Hasan, Alizar (CV. ITTC INDONESIA, 2022)
Indonesian citizens aged 17 years and over have an Identity Card (KTP) as their iden- tity. Children also have their own identity cards. The government has implemented MCH by issuing Minister of Home Affairs Regulation Number 2 of 2016 concerning Child Identity Cards. Permendagri Number 67 of 2020, the central government sets a target in achieving the Issuance of Child Identity Cards (KIA) for Provinces and Regencies/Cities throughout Indonesia. The targets that must be realized by Provinces and Municipalities from 2020- 2024 are: 20% in 2020, 30% in 2021, 40% in 2022, 50% in 2023, 60% in 2024. MCH Policy in the City Payakumbuh is still not fully known by the public. Some of the people do not know about the existence of MCH and the benefits of MCH. For people who already know about MCH, they also have a lack of awareness to manage MCH where people think MCH is not really needed, especially for children under 5 years old where all children’s activities are under the supervision of their parents. So that the issuance of MCH in Payakumbuh is still low. In addition to the lack of public knowledge about MCH, the community is also reluctant to take their children to the Population and Civil Registration Office on the grounds that the children are in school, the location of the Population and Civil Registration Office is quite far or the community lacks time to take their children so they can have a Child Identity Card ( KIA) because they work. The purpose of this study is to describe the effectiveness of the ball pick-up service carried out by the Population and Civil Registration Service in increasing MCH ownership and to find out the supporting factors and inhibiting factors in the Payakumbuh City Population and Civil Registration Service. This type of research is qual- itative research In the study, it was found that the number of residents aged 0-17 years less than 1 day who had a Child Identity Card (KIA) in Payakumbuh City was quite a lot and almost met the targeted MCH ownership standards. This is sufficient to prove that the MCH services provided are adequate by implementing the Ball Pick-up program, namely direct services to various places in Payakumbuh City including the Kelurahan office, schools and others to provide direct services with the aim of making it easier for the community to manage MCH. However, the services provided are still experiencing various kinds of obstacles where the ball pick-up service has not been scheduled due to an inadequate budget, besides that the facilities and infrastructure are still inadequate. to the center and the lack of socializa- tion specifically to the community regarding the importance of MCH so that the community considers MCH as a form of service for population administration documents that are less important so they are lazy to manage it. Keywords : Effectiveness, Ball Pick-up Service, Child Identity Card (KIA)